The Effectiveness of Red Onion Compresses in Reducing Joint Pain Intensity in Elderly Patients with Gout Arthritis - Istiawati, Ajeng; Sutrisno; Alfi Irawan, Anjas; Rice, Hernanda (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Gout arthritis is a condition that occurs due to elevated uric acid levels in the blood beyond normal limits, commonly seen in the elderly, characterized by joint pain. Based on data from the Natar Elderly Care Home, there are 15 elderly individuals with gout arthritis experiencing joint pain. Pain associated with gout arthritis can be managed through pharmacological therapy, such as medication, as well as non-pharmacological therapy, one of which is red onion compresses. This non-pharmacological approach is considered safer and has fewer side effects, particularly for the elderly. This study focuses on evaluating the effectiveness of red onion compresses in reducing joint pain in elderly individuals with gout arthritis at the Natar Elderly Care Home. Method: The method used in this study is a quantitative method with a quasi-experimental design, specifically a single-group pre-post test. The sample consists of 15 elderly individuals selected using purposive sampling. Pain levels were measured using the Numeric Rating Scale (NRS), and data were analyzed using a paired sample t-test. Result: Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant difference between pre- and post-application pain levels. This indicates that the intervention is effective in reducing joint pain in elderly gout patients. Conclusion: The application of red onion compresses has been proven effective as a non-pharmacological therapy for managing joint pain in elderly individuals with gouty arthritis. It is hoped that this intervention can be implemented sustainably at the Natar Elderly Care Home as an alternative pain management option for the elderly.